Moxibustion inhibits interleukin-12 and tumor necrosis factor alpha and modulates intestinal flora in rat with ulcerative colitis - Wang, Xiao-Mei (Baishideng Publishing Group Co., Limited, 2012)
AIM: To investigate the effect of moxibustion on intestinal flora and release of interleukin-12 (IL-12) and tumor necrosis factor-α (TNF-α) from the colon in rat with ulcerative colitis (UC). METHODS: A rat model of UC was established by local stimulation of the intestine with supernatant from colonic contents harvested from human UC patients. A total of 40 male Sprague-Dawley rats were randomly divided into the following groups: normal (sham), model (UC), herb-partition moxibustion (HPM-treated), and positive control sulfasalazine (SA-treated). Rats treated with HPM received HPM at acupuncture points ST25 and RN6, once a day for 15 min, for a total of 8 d. Rats in the SA group were perfused with SA twice a day for 8 d. The colonic histopathology was observed by hematoxylin-eosin. The levels of intestinal flora, including Bifidobacterium, Lactobacillus, Escherichia coli (E. coli), and Bacteroides fragilis (B. fragilis), were tested by real-time quantitative polymerase chain reaction to detect bacterial 16S rRNA/DNA in order to determine DNA copy numbers of each specific species. Immunohistochemical assays were used to observe the expression of TNF-α and IL-12 in the rat colons. RESULTS: HPM treatment inhibited immunopathology in colonic tissues of UC rats; the general morphological score and the immunopathological score were significantly decreased in the HPM and SA groups compared with the model group [3.5 (2.0-4.0), 3.0 (1.5-3.5) vs 6.0 (5.5-7.0), P < 0.05 for the general morphological score, and 3.00 (2.00-3.50), 3.00 (2.50-3.50) vs 5.00 (4.50-5.50), P < 0.01 for the immunopathological score]. As measured by DNA copy number, we found that Bifidobacterium and Lactobacillus, which are associated with a healthy colon, were significantly higher in the HPM and SA groups than in the model group (1.395 ± 1.339, 1.461 ± 1.152 vs 0.045 ± 0.036, P < 0.01 for Bifidobacterium, and 0.395 ± 0.325, 0.851 ± 0.651 vs 0.0015 ± 0.0014, P < 0.01 for Lactobacillus). On the other hand, E. coli and B. fragilis, which are associated with an inflamed colon, were significantly lower in the HPM and SA groups than in the model group (0.244 ± 0.107, 0.628 ± 0.257 vs 1.691 ± 0.683, P < 0.01 for E. coli, and 0.351 ± 0.181, 0.416 ± 0.329 vs 1.285 ± 1.039, P < 0.01 for B. fragilis). The expression of TNF-α and IL-12 was decreased after HPM and SA treatment as compared to UC model alone (4970.81 ± 959.78, 6635.45 ± 1135.16 vs 12333.81 ± 680.79, P < 0.01 for TNF-α, and 5528.75 ± 1245.72, 7477.38 ± 1259.16 vs 12550.29 ± 1973.30, P < 0.01 for IL-12). CONCLUSION: HPM treatment can regulate intestinal flora and inhibit the expression of TNF-α and IL-12 in the colon tissues of UC rats, indicating that HPM can improve colonic immune response.